Design of a Web-Based Regional Food Ordering Information System at Seribu Rasa Restaurant - Ahmad Fadhil Kurniahadi Al Jufri; Sagala Alex Paskalis; Novi Rukhviyanti (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The rapid development of information technology has presented significant opportunities for the culinary industry to improve operational efficiency and customer satisfaction. Seribu Rasa Restaurant, offering regional Indonesian specialities, faces challenges with its manual order management system, leading to long queues, extended waiting times, and limited access to menu information. This highlights the importance of adopting a web-based information system to enhance customer experience and business efficiency. This study aims to design a web-based food ordering information system for Seribu Rasa Restaurant to simplify the ordering process, expedite transactions, and improve data management. Using the Waterfall methodology, the research followed a systematic approach comprising requirements analysis, system design, implementation, testing, and maintenance. Data collection was conducted through interviews with restaurant management, observation of business processes, and a literature review. The system was developed with modern web technologies such as HTML, CSS, and JavaScript, with MySQL for database management. The results show that the developed system enables customers to easily browse menus, place orders, and make integrated payments online. System testing indicates that key features, including menu browsing, order placement, and online payment, function effectively and meet user needs.